Dietary Lactobacillus fermentum and Bacillus coagulans Supplementation Modulates Intestinal Immunity and Microbiota of Broiler Chickens Challenged by Clostridium perfringens - Guo, Shuangshuang; Xi, Yu; Xia, Yi; Wu, Tao; Zhao, Di; Zhang, Zhengfan; Ding, Binying (Frontiers in Veterinary Science, 2021)
Preventative effects of Lactobacillus fermentum and Bacillus coagulans against Clostridium perfringens infection in broilers have been well-demonstrated. The present study was conducted to investigate the modulation of these two probiotics on intestinal immunity and microbiota of C. perfringens-challenged birds. The 336 one-day-old broilers were assigned to four groups with six replicates in each group. Birds in the control were unchallenged and fed a basal diet, and birds in the three challenged groups were dietary supplemented with nothing (Cp group), 1 × 109 CFU/kg of L. fermentum (Lf_Cp group), or 1 × 1010 CFU/kg of B. coagulans (Bc_Cp group). Challenge was performed from days 14 to 20, and samples were collected on days 21 and 28. Challenge upregulated interleukin (IL)-1β and transforming growth factor (TGF)-β4 mRNA expression in jejunum on day 21, which was downregulated by B. coagulans and L. fermentum, respectively (P < 0.05). Both probiotic groups upregulated jejunal IL-1β, interferon (IFN)-γ, IL-17, and TGF-β4 on day 28 as well as IFN-γ on day 21 (P < 0.05). The Bc_Cp group increased CD3+ T cell counts in the jejunal crypt on day 21 (P < 0.05). Challenge decreased the ileal ACE index on day 21 and cecal microbial richness on day 28, which were increased by probiotic treatments, and ileal bacterial richness decreased in the Bc_Cp group on day 28 (P < 0.05). Only ileal microbiota on day 21 was distinctly affected with an R-value at 0.3116 by ANOSIM analysis (P < 0.05). Compared with the control, ileal Firmicutes increased on day 21, and ileal Bacteroidetes and cecal Proteobacteria decreased on day 28 in challenged groups (P < 0.05). Challenge increased Romboutsia spp. in the ileum as well as unclassified f_Lachnospiraceae and Ruminococcus_torques group in the cecum, and decreased Lactobacillus spp. in the ileum on day 21, which were all conversely modulated by L. fermentum (P < 0.05). Challenge increased amino acid metabolism of ileal microbiota and membrane transport of cecal microbiota, and decreased amino acid metabolism of cecal microbiota on day 21, which were conversely regulated by both probiotics (P < 0.05). In conclusion, L. fermentum and B. coagulans attenuated the intestinal inflammation and microbial dysbiosis soon after C. perfringens challenge.